The Biology and Natural History of Aphaenogaster rudis. (19th February 2012) - Lubertazzi, David
Abstract : Workers from the genus Aphaenogaster are among the most abundant ants in the hardwood forests of eastern North America. The biology of these so-called rudis -group ant species, including details about their sociometry, productivity, natural history, and behavior, are synthesized here using published and newly collected data. The latter was collected, in part, using an artificial field nest, and its construction and use are explained. Ants of the rudis group occur in high densities in forest habitats (0.5–1.3 nests m 2 ), have moderate sized colonies (population means from 266 to 613 workers per nest), and are keystone seed dispersers. Many aspects of their life history and behavior follow an annual cycle that tracks seasonal changes. These include foraging, reproduction, the production of new workers and nest migrations. This synthesis highlights what is known about these ants and reveals gaps in our knowledge that require further study.